Literasi Digital Dan Inovasi Bisnis Sebagai Faktor Pendukung Keunggulan Kompetitif Dan Eksistensi Usaha Mikro - Frida Anisawati; Agus Sumanto; Farida Rahmawati (Universitas Hamzanwadi, 2026)
This study aims to analyze the effect of digital literacy and business innovation on the sustainability of micro enterprises in Malang Regency, with competitive advantage as a mediating variable. Micro enterprises face various challenges, particularly limited access to capital and uneven digital transformation. The study employs a quantitative explanatory approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The population consists of 31,478 micro enterprises, with a sample of 395 respondents determined using the Slovin formula and probability sampling techniques. Data were collected through questionnaires using a 5-point Likert scale. The results indicate that digital literacy has a positive but not significant effect on the sustainability of micro enterprises, while business innovation has a positive and significant effect. Competitive advantage significantly mediates the relationship between digital literacy and business innovation on the sustainability of micro enterprises. These findings suggest that digital literacy alone does not guarantee business sustainability without being supported by competitive advantage and innovation. The model shows an R² value of 86.8%, indicating very strong predictive power.